Peran Guru PAI dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SMA Negeri 15 Makassar - Ruslan; Hakim, Ahmad; Hasan, Salim (Journal of Gurutta Education, 2024)
Learning to read the Quran is one of the subjects in Islamic Religious Education in schools. Islamic Religious Education serves as a means of knowledge transformation in the religious aspect (cognitive aspect), as a tool for transforming norms and moral values to shape attitudes (affective aspect), playing a role in controlling behavior (psychomotor aspect), thus creating a complete human personality. The aim of this research is to determine (1) the role of Islamic Religious Education (PAI) teachers in enhancing the Quran reading abilities of students at SMAN 15 Makassar and (2) the supporting and inhibiting factors affecting the role of PAI teachers in improving Quran reading abilities. The researcher used a qualitative approach, employing data collection techniques such as observation, interviews, and documentation. Data sources were obtained from the school principal, PAI teachers, and students of SMAN 15 Makassar. The data processing involved three stages: data reduction, data display, and verification/conclusion. The results showed that the role of PAI teachers in enhancing students' Quran reading abilities includes providing motivation, implementing effective methods, and serving as a learning source and guide. The methods used for improving students' Quran reading abilities are Iqro' method, demonstration method, and memorization method. Factors influencing students' Quran reading abilities consist of supporting factors such as parental support, teacher support, and a positive environment. In contrast, inhibiting factors include the use of social media and students' lack of awareness regarding the importance of learning to read the Quran